New director ready to refine chamber image - Williams, Curtis (Raton, NM Raton Range, 1995)
Article is about the new Chamber Director Wood Mitchell.
Newspaper article + Photograph of Woody Mitchell
Master list item #: 8
File location is in the Raton file Cabinet
Keywords: Woody, Mitchell -- Executive Director; Vanderpool, Pat; Seis, Mary; Raton Chamber and Economic Develpment Council; Economic Development; Local History; Life and Customs; Job Development; New Director; Local Business; Raton, New Mexico